استخدام البروبوفول مع الريمي فنتانيل لتسهيل تطبيق الماسك الحنجري في العمليات الجراحية القصيرة والمتوسطة. (Latakia University Journal -Medical Sciences Series, 2019)
شملت الدراسة 100 مريض من المقبولين في مشفى الأسد الجامعي باللاذقية خلال المدة ما بين             2008ـ 2007 ، لإجراء عمليات  جراحية قصيرة ومتوسطة المدة. بلغ عدد الذكور في عينة الدراسة (56) بنسبة  56% وعدد الإناث (44) بنسبة  44% قمنا بتقسيم مرضى الدراسة إلى مجموعتين: المجموعة(A): تلقت البروبوفول مع الريمي فنتانيل حقناً وريدياً قبل تطبيق الماسك الحنجري وشكلت 50 مريضاً [2]. المجموعة(B): تلقت البروبوفول مع الريمي فنتانيل والسوكسونيل كولين حقناً وريدياً قبل التنبيب الرغامي وشكلت  50مريض [2]. ولدى تقييم نتائج تطبيق الماسك الحنجري ومقارنتها مع التنبيب الرغامي ، أظهرت النتائج أن المشاركة (بروبوفول – ريمي فنتانيل) سهلت تطبيق الماسك الحنجري من دون الحاجة لاستخدام مرخٍ عضليٍ وأمنت ثباتاً هيمو ديناميكياً أكبر مقارنة مع التنبيب الرغامي. Our study included 100 patients from those who were admitted to AL-Assad University Hospital (LATTAKIA) during 2007-2008 for the short and medium surgical operation. The male patients were 50 (50%) and the female ones 50 (50%). We divided our patients into two groups: Group A accounted for 50 patients who received propofol with remifentanil venous before the insertion of the Laryngeal mask Group B accounted for 50 patients who received propofol with remifentanil and succinylcholine venous before intubation. We have evaluated the results of the insertion of the Laryngeal mask and compared them with intubation. The results showed that the sharing (propofol – remifentanil) facilitate the insertion of the Laryngeal mask without the use of muscle relaxants and provided bigger hemodynamic stability when compared with Intubation.